Teaching and Memory: Why corporal punishment persists at schools - training for transgression? - Davids, Mogamat Noor (South African Journal of Higher Education, 2016)
Corporal punishment at schools often causes consternation and public outcry despite its abolition almost two decades ago. The Department of Education published “Alternatives to corporal punishment” (2000) which largely proves ineffective at especially schools in poor communities. This article reports on a study conducted by student teachers in Kwazulu-Natal, a province where corporal punishment is still rife. The article addresses the following questions: What are common memories of corporal punishment and, how beneficial were student teachers’ experiences and memories of corporal punishment in assisting them to develop a pedagogical perspective for future practice? Data were collected by using interview questionnaires (N=70) and five reflective student reports. Schooling memories of adults were captured by conducting an interview questionnaire in which ‘corporal punishment’ emerged as a major memory theme. Five student teachers were purposely selected to write a reflective report in response to a set of questions relating to their experiences of corporal punishment. The paper concludes that by employing memory as a reflective discursive background, negative memories can be destabilized and disrupted to initiate new pedagogical practices. Valuable lessons were learnt to navigate the challenging terrain of corporal punishment which epitomizes the persistent violation of children’s rights at many schools. Key words: corporal punishment teacher education pedagogy discursive practices Schools Act memory reflexivity